A retrospective review of the adnexal outcome after detorsion in premenarchal girls - Abdullah Yildiz; Başak Erginel; Melih Akin; Cetin Ali Karadağ; Nihat Sever; Canan Tanik; Arzu Canmemiş; Ali Ihsan Dokucu (Wolters Kluwer Medknow Publications, 2014)
Background: The aim of this study was to report our results on premenarchal girls with adnexal torsion who were treated with different approaches. Materials and Methods: Twenty-six adnexal torsions in children were analysed retrospectively. Group 1 included cases of oophorectomy for the twisted adnexa. Group 2 contained the patients with adnexal torsion who untwisted either with a laparoscopic or open approach. Postoperative restoration of ovarian function was evaluated by Doppler ultrasound at the 6 th month. All oophorectomy and biopsy specimens were also evaluated. Results: Group 1 consisted of eleven cases that underwent oophorectomy due to gangrenous change and haemorrhagic infarction. Histology was of a mature teratoma in two cases and haemorrhagic necrosis due to torsion in seven. Group 2 consisted of 15 patients. In 10 out of 15 patients, preoperative biopsy is performed in which their histology revealed haemorrhagic necrosis in eight cases, and simple cyst with a benign nature in two cases. In all of the 10 untwisted adnexas, postoperative radiological imaging showed complete recovery with normal follicular development. No malignancy or increased tumour markers were noted in both groups. Conclusion: Adnexas can be left in place regardless of the preoperative degree of necrosis. Biopsy can be added to the procedure to rule out malignancy.